2022
DOI: 10.3389/fpsyt.2022.893505
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Infant Bonding and Its Associated Factors Among Mothers in the Postpartum Period, Northwest Ethiopia, 2021

Abstract: BackgroundThe emotional bond that a mother senses to her infant is essential to their social, emotional, and cognitive development. Understanding the level of mother-infant bonding plays an imperative role in the excellence of care. However, in Ethiopia, there is a paucity of information about mother-infant bonding in the postpartum period.ObjectiveThis study aimed to assess the level of mother-infant bonding and its associated factors among mothers in the postpartum period, Debre Tabor Town Northwest Ethiopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
2
6
1
Order By: Relevance
“…This is in agreement with other studies that showed higher bonding impairment in first-time mothers than mothers who already had other children [13,24,44]. Similar to other studies, other maternal factors like mode of delivery, antenatal attendance, birth complications, and skin-to-skin contact had no significant effect on maternal-infant bonding [2,45,47]. However, it should be noted that two previous studies showed that skin-to-skin contact between mother and baby enhances maternal-infant bonding [6,47].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in agreement with other studies that showed higher bonding impairment in first-time mothers than mothers who already had other children [13,24,44]. Similar to other studies, other maternal factors like mode of delivery, antenatal attendance, birth complications, and skin-to-skin contact had no significant effect on maternal-infant bonding [2,45,47]. However, it should be noted that two previous studies showed that skin-to-skin contact between mother and baby enhances maternal-infant bonding [6,47].…”
Section: Discussionsupporting
confidence: 92%
“…The PBQ was specifically chosen to measure mother–infant bonding in this study because it is a commonly used measure that has been shown to be reliable and valid across different countries, languages, and cultures [ 11 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In Africa, it has been used in Egypt [ 15 ] and Ethiopia [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, poor MIB has been noted as a risk factor for the growth and development of children, similar to child neglect or abuse [ 6 ]. In recent years, studies have reported that a large number of mothers experience MIB disorder [ 7 11 ]. In Japan, for instance, MIB disorder reportedly affects 10–21% of mothers [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%